Caudal pulmonary hypostasis and edema due to upright body position after death. (December 2020) - Hagita, Tomoaki; Shiotani, Seiji; Kuma, Natsuyo; Toyama, Nagahiro; Tominaga, Naoki; Miyazaki, Hiromi; Ogasawara, Nobuhiko
Highlights: Postmortem CT (PMCT) of two sediment disaster victims were performed. They were found buried upright in sediment. PMCTs showed hypostasis and postmortem edema on the caudal portion of the lungs.